2014
DOI: 10.1007/s10509-014-1884-0
|View full text |Cite
|
Sign up to set email alerts
|

On the radiative and thermodynamic properties of the cosmic radiations using COBE FIRAS instrument data: I. Cosmic microwave background radiation

Abstract: Use formulas to describe the monopole and dipole spectra of the Cosmic Microwave Background (CMB) radiation, the exact expressions for the temperature dependences of the radiative and thermodynamic functions, such as the total radiation power per unit area, total energy density, number density of photons, Helmholtz free energy density, entropy density, heat capacity at constant volume, pressure, enthalpy density, and internal energy density in the finite range of frequencies v 1 ≤ v ≤ v 2 are obtained. Since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Some new strategies were needed to decode SARS-COV-2. In the vast universe, number law showed up in everything, such as from the redshift of cosmic microwave background radiation to the number of C. elegans cells, from the quantum number of particle physics to the life cycle of periodic cicadas 4,5 . These studies revealed that number theory could bridge the three elds of mathematics, physics and biology 6,7 .…”
Section: Mainmentioning
confidence: 99%
“…Some new strategies were needed to decode SARS-COV-2. In the vast universe, number law showed up in everything, such as from the redshift of cosmic microwave background radiation to the number of C. elegans cells, from the quantum number of particle physics to the life cycle of periodic cicadas 4,5 . These studies revealed that number theory could bridge the three elds of mathematics, physics and biology 6,7 .…”
Section: Mainmentioning
confidence: 99%
“…On varying parameters d, h and α o , masses of eight different stars were regained given in Table 1. The acceptable values for ρ 0 and P r 0 are given in Table 1 by fixing α 1 = 0.931 and = 7.5756 × 10 −16 [32]. Table 2 contains varying values of ρ, P r , m, E 2 and υ 2 from central point to boundary of stars.…”
Section: Properties Of New Solutionmentioning
confidence: 99%
“…In conclusion of this paragraph, it is essential to note that the analytical expressions derived above in the case of black-body radiation, when 1 and 0 0   a a i , take a well-known expressions [48].…”
Section: Polylogarithmic Representation Of Thermal Radiative Properti...mentioning
confidence: 99%
“…is the total energy density of blackbody radiation in the finite frequency range of the spectrum [48].…”
Section: General Relationships For Thermal Radiative and Thermodynami...mentioning
confidence: 99%